Thailand : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper analyzes factors that could bring inflation back to target in Thailand. The paper estimates a hybrid New Keynesian Phillips curve with time varying parameters to gauge the quantitative role of (long-term) inflation trends, economic slack, and import price inflation in shaping inflation dynamics. The analysis reveals some important changes in Thailand's inflation dynamics. It suggests that the impact of lower import prices was a major factor behind the decline in headline inflation in 2015, with low oil prices the largest contributor to inflation dynamics. Monetary policy easing, within a broader expansionary policy mix, should help bring inflation back to target.